(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
The aim of this review is to identify the methodological and interventor characteristics of occupational stress management programs. Sixty one studies were found by electronic data bases. Subsequently they were codified and their data were analysed by the statistical program SPSS. The results indicated that the programs have been implemented mainly in education and health contexts, with small samples, quasi-experimental and experimental designs, evaluation of individual dependent variables and cognitive-behavioral techniques. Evidences that multicomponent content programs are more effective in the reduction of individual indicators, as anxiety and depression, were found. Implications tonewstudies and application are discussed.